SFPQ and NONO suppress RNA:DNA-hybrid-related telomere instability - Eleonora Petti (Nature Portfolio, 2019)
LncRNA TERRA forms RNA-DNA hybrids at telomere sites leading to telomere instability. Here the authors identify the RNA interacting factors NONO and SFPQ as proteins that interact with TERRA and telomere chromatin and reveal putative roles for these factors in telomere integry maintenance by interfering with RNA:DNA hybrid formation.